MANAJEMEN KESISWAAN DAN BIMBINGAN KONSELING DALAM PERSPEKTIF PENDIDIKAN KARAKTER - Agus Salim Chamidi (Prodi MPI IAINU Kebumen, 2017)
Management of students and guidance and counceling becomes one important component in management of school/madrasah. It becomes very important when it is associated with the character learning in Indonesia nowadays. This writing tries to explain them through one aspect of management, that is planning. Planning in recruiting new students is so important and vital as a part of process of management of students and guidance and counceling in school/madrasah. All activities associating with recruiting new students, both management and administrative, becomes like a success key at first for process of school/madrasah management sustainably. Keywords: management of students, management guidance and couceling, character learning, planning.